Induction of superficial zone protein (SZP)/ lubricin/PRG 4 in muscle-derived mesenchymal stem/progenitor cells by transforming growth factor-b1 and bone morphogenetic protein-7 - Andrades-Gómez, José Antonio; Motaung, Shirley C; Jiménez-Palomo, Pedro; Claros-Gil, Silvia; López-Puerta, José M.; Becerra-Ratia, José; Schmid, Thomas M.; Reddi, A. Hari (Springer Nature, 2012)
Introduction Articular cartilage (AC) is an avascular tissue with precise polarity and organization. The three distinct zones are: surface, middle and deep. The production and accumulation of the superficial zone protein (SZP), also known as lubricin, by the surface zone is a characteristic feature of AC. To date, there is a wealth of evidence showing differentiation of AC from mesenchymal stem cells. Most studies that described chondrogenic differentiation did not focus on AC with characteristic surface marker SZP/lubricin. The present investigation was initiated to determine the induction of SZP/lubricin in skeletal muscle-derived mesenchymal stem/progenitor cells (MDMSCs) by transforming growth factor-β1 (TGF-β1) and bone morphogenetic protein-7 (BMP-7). Methods MDMSCs were cultured as a monolayer at a density of 1 × 105 cells/well in 12-well tissue culture plates. Cell cultures were treated for 3, 7 and 10 days with TGF-β1 and BMP-7. The medium was analyzed for SZP. The cells were used to isolate RNA for RT-PCR assays for SZP expression. Results The SZP/lubricin increased in a time-dependent manner on Days 3, 7 and 10 in the medium. As early as Day 3, there was a three-fold increase in response to 3 ng/ml of TGF-β1 and 300 ng/ml of BMP-7. This was confirmed by immunochemical localization of SZP as early as Day 3 after treatment with TGF-β1. The expression of SZP mRNA was enhanced by TGF-β1. Conclusions The present investigation demonstrated the efficient and reproducible induction of SZP/lubricin accumulation by TGF-β1 and BMP-7 in skeletal MDMSCs. Optimization of the experimental conditions may permit the utility of MDMSCs in generating surface zone-like cells with phenotypic markers of AC and, therefore, constitute a promising cell source for tissue engineering approaches of superficial zone cartilage.
Keywords: Cartílagos; Mesenchymal stem cells; Articular cartilage; Autologous chondrocyte implantation; Surface zone; Tissue engineer cartilage